2014
DOI: 10.1063/1.4862783
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting of drifting filamentous macroalgae in the Baltic Sea: An energy assessment

Abstract: Red seaweed derived polysaccharides, a novel marine resource for bio-ethanol production J. Renewable Sustainable Energy 6, 033122 (2014); 10.1063/1.4880515 Multifrequency species classification of acoustic-trawl survey data using semi-supervised learning with class discovery Eutrophication combined with climate change has caused ephemeral filamentous macroalgae to increase and drifts of seaweed cover large areas of some Baltic Sea sites during summer. In ongoing projects, these mass occurrences of drifting fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A number of pilot projects in the Baltic Sea area have tested methods to produce biogas from beach cast. For instance, the Swedish municipality Trelleborg tested biogas production through anaerobic digestion in a customized biogas plant, using the residue as biofertilizer in agriculture (Risén et al 2014). The results show that it is possible to achieve a positive energy balance for the biogas production (Risén et al 2014), but also that there are considerable practical challenges including handling of the sand mixed in with the seaweed and the high salt, sulfur and sometimes cadmium levels in the biomass that limit its usefulness as fertilizer.…”
Section: Beach Wrack As a Potential Bioresourcementioning
confidence: 99%
See 1 more Smart Citation
“…A number of pilot projects in the Baltic Sea area have tested methods to produce biogas from beach cast. For instance, the Swedish municipality Trelleborg tested biogas production through anaerobic digestion in a customized biogas plant, using the residue as biofertilizer in agriculture (Risén et al 2014). The results show that it is possible to achieve a positive energy balance for the biogas production (Risén et al 2014), but also that there are considerable practical challenges including handling of the sand mixed in with the seaweed and the high salt, sulfur and sometimes cadmium levels in the biomass that limit its usefulness as fertilizer.…”
Section: Beach Wrack As a Potential Bioresourcementioning
confidence: 99%
“…For instance, the Swedish municipality Trelleborg tested biogas production through anaerobic digestion in a customized biogas plant, using the residue as biofertilizer in agriculture (Risén et al 2014). The results show that it is possible to achieve a positive energy balance for the biogas production (Risén et al 2014), but also that there are considerable practical challenges including handling of the sand mixed in with the seaweed and the high salt, sulfur and sometimes cadmium levels in the biomass that limit its usefulness as fertilizer. The Danish municipality Solrød recently constructed a biogas plant that was specifically designed for anaerobic degradation of beach cast seaweed mixed with manure and carrageenan and pectin production waste.…”
Section: Beach Wrack As a Potential Bioresourcementioning
confidence: 99%
“…The collection or harvesting of marine macroalgae from aquatic environments requires efficient, simple and affordable methods. Marine macroalgae can be harvested in different ways, either manually or mechanically, depending on the biomass linkage and whether they are accumulated on the beach or floating in open or shallow waters [ 53 , 146 , 161 ]. Macroalgae cultivation facilities represent a source of experience regarding macroalgae harvesting from water.…”
Section: Occurrence Of Marine Eutrophication and Improvement Of Comentioning
confidence: 99%
“…The energy analysis for whole process of hydrogen fermentation (combined dark and photo fermentation) from algal biomass has been rarely reported. A recent study by Risen et al indicated the whole process of biogas production from waste macroalgae in the Baltic Sea consumes 30-40% of energy content in biogas [157]. More studies on mass, energy and economical balances of the whole process should be carried out in the future.…”
Section: Potential Of Fermentative Hydrogen Production From Algal Biomentioning
confidence: 98%
“…A pilot project in Sweden has been established to harvest drifting filamentous macroalgae from shorelines in Baltic Sea. The harvested macroalgal biomass may be used for biogas production [157].…”
Section: Hydrogen Fermentation Of Algal Biomass At Optimized Componentsmentioning
confidence: 99%